National Monetary Policy, Internatinal Economic Instability and Feeback Effects - An Overinvestment View - Andreas Hoffmann; Gunther Schnabl (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2011)
The paper explains internationally transmitted boom-and-bust cycles as the outcome of excessive liquidity supply based on the credit boom theories of Hayek (1929; 937), Mises (1912) and Minsky (1986). We show how too expansionary monetary policies cause distortions in the economic structure and boom-and-bust cycles on both a national and an international level. Feedback effects of crises in periphery countries on center countries are shown to trigger a new round of monetary expansion in large countries, which provide international currencies to an asymmetric world monetary system. Crisis and contagion in globalized goods and financial markets indicate the limits of purely national monetary policies, which solely focus on domestic consumer prices and output. This makes the case for monetary policies in large countries, which take responsibility for the long-term effects of monetary policy on goods and financial markets in both home and foreign as put forward by Hayek (1937).
urn:nbn:de:gbv:27-20131126-115054-4
Keywords: 330; Feeback Effects; Economic Instability; Geldpolitik; Liquidität; Makroökonomischer Einfluss; Konjunktur; Periphere Region; Konjunkturzusammenhang; Theorie